RELATIONSHIP BETWEEN PARENT’S ATTENTION, LEARNING FACILITIES, AND LEARNING MOTIVATION, WITH MATHEMATICS LEARNING OUTCOMES IN STUDENTS CLASS VIII AT SMP MUHAMMADIYAH PLERET BANTUL - Arif Romadhon; Abdul Taram (AdMathEduSt: Jurnal Ilmiah Mahasiswa Pendidikan Matematika, 2017)
Attention parents were low, inadequate learning facilities, as well as students 'motivation,  is still low allegedly associated with the results of students' mathematics learning. This study aims to determine the presence or absence of a positive and significant relationship between Parents Attention, Learning Facilities, and Motivation to learn the Mathematics Learning Outcomes of Students Class VIII at SMP Muhammadiyah Pleret on the Even Semester Academi Year 2015/2016. The population in this study were all students of class VIII SMP Muhammadiyan Pleret on the even Semester Academic Year 2015/2016 as many as 4 classes. The research sample is a class VIII A using random sampling techniques. Data collection techniques such as test and non-test techniques. Data collection instruments in the form of questions and questionnaires. Test instruments used are validity, reliability test, and test different power. The analysis prerequisite test including normality test, linearity test, and the test of independence. Analysis of data using correlation analysis and linear regression analysis. The results showed that there is a positive and significant correlation between parents attention, learning facilities, and motivation to learn the mathematics learning outcomes, multiple correlation coefficient (R) 0.7173, with the regression equation = , at the 5% significance level, obtained   at 9.5383 and  at 2,9063 means   . The percentage relative contribution of parents attention ,the relative contribution on learning facilities , and the relative contribution of learning motivation ,49%, and then effective contribution on parents attention  , the effective contribution of learning facilities  , and the effective contribution of learning motivation .